2017
DOI: 10.3390/nu9101152
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Micellar Incorporation and the Intestinal Cell Uptake of Cholecalciferol, 25-Hydroxycholecalciferol and 1-α-Hydroxycholecalciferol

Abstract: In the context of the global prevalence of vitamin D insufficiency, we compared two key determinants of the bioavailability of 3 vitamin D forms with significant biopotencies: cholecalciferol, 25-hydroxycholecalciferol and 1-α-hydroxycholecalciferol. To this aim, we studied their incorporation into synthetic mixed micelles and their uptake by intestinal cells in culture. Our results show that 1-α-hydroxycholecalciferol was significantly more solubilized into mixed micelles compared to the other forms (1.6-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…We first used the popular Caco-2 TC-7 intestinal cell model, which constitutionally expresses ABCB1 (26). We confirmed that these cells were able to efflux both neo-absorbed D 3 and 25(OH)D 3 to the apical medium, in line with our previous data (5,6). The fact that the efflux of both vitamin D forms could be impaired by PSC833, the reference inhibitor of ABCB1 activity, is taken as primary evidence that ABCB1 is involved in this process.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We first used the popular Caco-2 TC-7 intestinal cell model, which constitutionally expresses ABCB1 (26). We confirmed that these cells were able to efflux both neo-absorbed D 3 and 25(OH)D 3 to the apical medium, in line with our previous data (5,6). The fact that the efflux of both vitamin D forms could be impaired by PSC833, the reference inhibitor of ABCB1 activity, is taken as primary evidence that ABCB1 is involved in this process.…”
Section: Discussionsupporting
confidence: 85%
“…Vitamin D intestinal absorption has long been thought to occur through passive diffusion (4), but we have recently shown that membrane transporters of cholesterol, such as scavenger receptor class B type I (SRBI), CD36 molecule, and to a lesser extent, NPC1like intracellular cholesterol transporter 1 (NPC1L1), facilitate D 3 intestinal absorption (5) but not that of 25(OH)D 3 (6). In addition, the efflux of neo-absorbed D 3 (5) and 25(OH)D 3 (6) from Caco-2 cells into the apical medium in the presence of mixed micelles strongly suggests the existence of an active excretion of the vitamin D from the intestine into the lumen. Such luminal efflux is a key limiting process of the absorption of a large number and variety of lipids and xenobiotics, and its complete mechanism is poorly understood.…”
mentioning
confidence: 99%
“…Mixed micelles containing carotenoids were synthesized as previously described, with minor modifications. In summary, solvent solutions of carotenoids were first mixed with solvent solutions of micelle lipids and then the mixture was evaporated.…”
Section: Methodsmentioning
confidence: 99%
“…Apical efflux was assessed as previously described . First, the apical side of the cells was incubated during 4 h with carotenoid‐rich mixed micelles that contained around 10 µ m carotenoids.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, another study estimated the differences in the AUC after a bolus of the 2 metabolites; it showed that 25(OH)D3 increased vitamin D status 2–3 times more than vitamin D-3 (96). Recently, in a human cell line (Caco-2), 25(OH)D3 was taken up more efficiently than vitamin D-3, and more solubilized into mixed micelles by a factor of ∼1.8 (99).…”
Section: Vitamin Dmentioning
confidence: 99%